A Drop of Success – Internationalization Readiness of a Young Finnish Company - Jalanne, Joel (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study analyzes a young Finnish micro-sized firm that is attempting to reach internationalization readiness in the pre-internationalization stage. The purpose of this research is to analyze and better understand how a young firm reaches internationalization readiness in the pre-internationalization stage. Small firm internationalization is a vastly researched topic. Little emphasis has been placed on the specific antecedents that help the firm reach internationalization readiness in the pre-internationalization stage. The contribution of this research is thus two-fold. First, the research contributes to known theories of firm internationalization. Second, the research further extends knowledge related to how firms reach internationalization readiness specifically in the pre-internationalization stage. The theoretical background of the research involves the traditional stage theory (Uppsala model), pre-internationalization stage theory, international entrepreneurship theory and dynamic capabilities theory. With the help of these four relevant theories, empirical data was collected. The research method utilized in this study was a qualitative single case study combined with critical realist philosophy. The data analysis of this research was conducted using abduction in order to allow freedom in the analysis of the research findings. The empirical data was collected through semi-structured, face-to-face interviews. The key respondents in this study were the two managers of the case company. The findings of this study revealed four important themes from the case company’s perspective towards reaching internationalization readiness in the pre-internationalization stage. Extensive knowledge of the home market and target market were the two most important themes in this research. The next most relevant theme for reaching internationalization readiness in the pre-internationalization stage was the managers’ previous international business experiences. The final theme affecting the firm’s ability to reach internationalization readiness was the firm’s specific resources. Even though the research findings of this study are case sensitive, the research insights and explanations have the potential to be transferred to similar firms and contexts. Future research should therefore aim towards more longitudinal studies in which the context is emphasized. This should include a variety of firms in similar stages of internationalization and contexts. Future studies of this kind would be of great benefit to academia.